2009
DOI: 10.1160/th08-07-0474
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulant therapy in patients with mechanical heart valve and intracranial haemorrhage

Abstract: SummaryOptimal timing for restarting anticoagulant therapy after intracranial bleeding is a critical issue. The purpose of this systematic review is to summarize published studies on the management of oral anticoagulant therapy after intracranial bleeding secondary to the use of vitamin K antagonists in patients with a mechanical heart valve. A computer-assisted search of the MEDLINE and EMBASE electronic databases till January 2008 was performed. Two investigators independently performed study selection and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Resumption occurred after a median of 4.4 weeks (IQR 2. [3][4][5][6][7][8][9][10][11][12][13][14] in patients with intracerebral hemorrhage, compared with 6.4 weeks (IQR 3.6 -26) after subdural hematoma.…”
Section: Resumption Of Warfarinmentioning
confidence: 99%
See 1 more Smart Citation
“…Resumption occurred after a median of 4.4 weeks (IQR 2. [3][4][5][6][7][8][9][10][11][12][13][14] in patients with intracerebral hemorrhage, compared with 6.4 weeks (IQR 3.6 -26) after subdural hematoma.…”
Section: Resumption Of Warfarinmentioning
confidence: 99%
“…A recent systematic review of studies in patients with mechanical heart valves reached the same conclusion based on only 2 recurrent hemorrhages and 4 strokes. 14 Seven experts expressed the opinion that warfarin could be restarted in stable patients 3 to 10 days after intracranial hemorrhage. 15 We performed this study to address the timing of resumption of warfarin after intracranial hemorrhage and assess the risks and benefits both in patients who restarted warfarin and those who did not.…”
mentioning
confidence: 99%
“…Currently available data are contradictory. A review of 6 observational studies on oral anticoagulation in patients with mechanical valves concluded that restarting oral anticoagulation after 7 to 14 days appeared safe 6 ; however, a delay of reintroduction of warfarin until between 10 and 30 weeks has also been suggested. 2 Nevertheless, all studies, however, present a similar pattern: the probability of ICH recurrence is highest during the early phase after the index bleeding and decreases over time, whereas risk of ischemic events increases over time and will cross at some point in time.…”
mentioning
confidence: 99%
“…Until recently, expert opinion 1 as well as systematic reviews 2,3 were favoring early resumption, that is, after 3 to 14 days, of anticoagulation in stable patients. A retrospective study of 234 patients with warfarin-associated ICH concluded that the resumption should be delayed by 10 to 30 weeks to avoid the early high-risk period for recurrent hemorrhage, during which full anticoagulation appeared to increase this risk 5-fold.…”
mentioning
confidence: 99%
“…До недавнего времени мнение экспертов [1], а также данные систематических обзоров [2,3] свидетельство-вали в пользу скорейшего возобновления антикоагу-лянтной терапии у стабильных пациентов, т.е. через 3-14 дней.…”
unclassified